Prevalence and factors associated with prelacteal feeding in Western Nepal - Khanal, V.; Lee, Andy; Karkee, R.; Binns, Colin (Elsevier, 2014)
Background: Newborn infants are often given prelacteal feeds in Nepal despite government policies encouraging exclusive breastfeeding for the first six months of life. Aim: This study investigated the prevalence, reasons, types and factors associated with prelacteal feeding in the south-western region of Nepal. Methods: Information on prelacteal feeding was obtained from 735 recently delivered women who were recruited for a prospective community-based cohort study conducted during 2014 in the Rupandehi district of Nepal. Factors associated with prelacteal feeding were assessed using logistic regression analysis. Findings: A total of 225 (30.6%) mothers reported giving prelacteal feeds to their infants. The most popular prelacteal food was formula milk (41.7%), followed by cow or buffalo milk (26.6%), and sugar/glucose water (12.4%). Caesarean delivery (17.3%), cultural preference (16.4%) and being tired after childbirth (10.6%) were the most commonly cited reasons. Almost half (48%) of the mothers were advised by their mother/mother-in-law on prelacteal feeding method. Higher parity (adjusted odds ratio (OR) 2.05; 95% confidence interval (CI) 1.18-3.54), low birthweight (OR 1.97; 95% CI 1.23-3.16), caesarean delivery (OR 3.70; 95% CI 2.37-5.80) and wealthy status (OR 2.49; 95% CI 1.52-4.06) were associated with prelacteal feeding. Conclusion: Nearly one-third of the infants in this study were given prelacteal feeds. Future breastfeeding promotion programmes should focus on the mothers with low birthweight infants, of high parity, from a wealthy family and those who had caesarean delivery.